Influence of the labor quality of life on the employee performance of public hospitals from Mexico: a vision based on the team management - Marivel Lumbreras-Guzmán; Irma Alejandra Hernández-Vicente; Pablo Méndez-Hernández; Libia Darina Dosamantes-Carrasco; Margarita Cervantes-Rodríguez; Argelia García-Elizalde; Héctor Manuel Cortez-Yacila (Instituto Nacional de Salud Pública, 2019)
Objective. To assess the relationship between labor quality of life (LQL) and organizational workers performance (OWP) from seven public hospitals, analyzing the influence of the personnel management (PM) as mediator of this relationship. Materials and methods. A cross-sectional study was conducted in 866 professionals and managers of public hospitals from Tlaxcala and Mexico City. The LQL was assessed with a validated questionnaire, OWP with 34 indicators, and PM with an instrument designed for this study. Results. Mean scores of LQL, were significantly lower among workers from Tlaxcala. Participants who perceived an adequate PM, they increased at 2.7 times their likelihood of having highest LQL, and participants categorized in the high LQL presented 69% higher likelihood of having an adequate OWP. Conclusions. The appropriate PM was associated with greater LQL, showing to be a mediator variable between the positive relationship of CVL and the OWP.